Verre Cassé d'Alain Mabanckou entre oralité et écriture ou la transmission d'une mémoire transculturelle - Cescutti, Tatiana (Laboratorio critico: rivista di francesistica, 2012)
This article aims to show that spoken and written registers are combined in Alain Mabanckou's novel Verre Cassé in such a way that the text becomes a site of transcultural memory. The focus is on an analysis of how the writing, full of intertextual references borrowed from Western and Black African culture, is invested with orality, on the one hand by drawing directly on the sources of the African oral tradition (storytelling and the art of griot oratory), and on the other by making frequent use of "deviant" French, namely, a language replete with Africanisms.